(untitled) (Ar-Raudhah: Journal of Islamic Religious Education, 2025)
This study aims to evaluate the Tahfidz Al-Qur’an Program at Pesantren Mahasiswa Dai Depok using the CIPP evaluation model (Context, Input, Process, Product). The evaluation was conducted to assess the extent to which the program has achieved its objectives and to identify strengths and weaknesses in its implementation. This research employed a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The evaluation results show that in terms of context, the program achieved a maximum score of 100%, indicating that the background and objectives of the program are highly relevant to the needs of the participants. The aspects of input, process, and product each received a score of 75%, suggesting that the program implementation is fairly good but still requires improvement in resource planning, activity execution, and final outcomes. Overall, the Tahfidz Al-Qur’an Program at Pesantren Mahasiswa Dai Depok falls into the “good” category with an average score of 81.25%. The findings recommend enhancing the quality of input, process, and product components to achieve more optimal results.